THE REPRESENTATION OF “THE OTHER” IN ANDREA LEVY’S SMALL ISLAND NOVEL - Asmara, Tusri Juni; Lubis, Indah Sari; Valiantien, Nita Maya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
This study examined Small Island novel by Andrea Levy as the object of the research. The aims of this research are to analyze the representation of “the Other” and how it portrayed in Small Island novel. To figure it out, this research used Orientalism theory to see how the orient was represented, especially used Tyson’s developmental theory from Said’s Orientalism as the indicators for the analysis. Moreover, this research used Kenan’s characterization theory to reveal how the representation was portrayed in the novel. This research used descriptive qualitative research method and Post-colonial approach to analyze the social issue of “the Other” that affected by European rules and colonization reflected in the novel. The result of this research shows that there are five negative representations of the orient. Those are difference, inferior, savage, backward, and undeveloped. Those representations were portrayed in two ways; direct and indirect presentation in the way of the character’s speech, external appearance and environment in the story.